The Constitutionality of the Electronic Information and Transaction Law: Towards Overcoming SARA Conflict on Social Media - Ismail Hasani; Halili Halili (Jurnal Konstitusi, 2021)
The subsistence of the Electronic Transaction and Information Law control and manage the illicit offenses related to the multiplication of concerns that hold Ethnicity, Religion, Race, and Intergroup (SARA) . Following the idea of law developed by practicality as a way of social regeneration. It is a legal normative investigation utilizing theoretical concurrence and laws. This research is a logical description by using qualitative information examination. The study revealed that content that contains SARA issues is referred to as a hatred statement, which can be construed as an act of communication, carried out by groups or individuals in the form of aggravation and endangered to throw the scandalous actor to prison for utmost six years and a fine of 1.000.000.000 rupiahs. Additionally, the accomplishment of the permissible authority of the Electronic Transaction and Information Law can be classified as non-implementation of the law authenticity establishment as shown from the culture that was not able to go after the rules made by law. It means that this law did not yet have a legal effect. This investigation advocates that society needs to behave by following the officially permitted rules, explained in the Electronic Transaction and Information Law.